Correlation of fecal egg counts of soil transmitted helminths with the worm load recovered after treatment among Filipinos. - Phansri, Wanna
Previous classifications of intensity of soil-transmitted helminths group appear not to be satisfactory when signs and symptoms are correlated with worm burden determined by the egg counts in feces, therefore, this study was undertaken to determine whether the soil-transmitted helminths in the Philippines are biologically different from the soil-transmitted helminths in other countries. The subjects included in this study came from San Andres, Metro Manila; San Pedro, Laguna and Victoria, Oriental Mindoro. The whole day fecal specimen was collected in 12 x 18 inches plastic bag from each subject and the egg counts were made using Kato-katz's modified thick smear technique. From the formed-stool, the fecal specimen was divided into 10 portions and the egg counts from each portion was done using the same technique. Treatment was given to the subject according to the kind of helminthic infection and the following day, the whole day feces was collected for 3 consecutive movements or 3 days. The adult worms expelled after treatment were collected, grouped and sexed. Results of this study show that there is a positive correlation of fecal egg counts of soil-transmitted helminths with the worm load recovered after treatment. The egg-laying capacity of trichuris and hookworm is similar to those previous studies. Due to some unexpelled female ascaris worms after treatment, the computed egg counts produced by 1 female ascaris is rather high, hence, we cannot conclude that the female ascaris worm in this country produces more eggs than the female ascaris worm in other countries. However, there are indications that ascaris in the Philippines seems to produce more eggs than ascaris in other countries. The sex ratio of ascaris was 1:0.92 trichuris was 1:1.21 and hookworm (Necator americanus) was 1:1.4. Eggs of soil-transmitted helminths appear to be homogenous in distribution in the feces. The proposed classifications of intensity of soil-transmitted helminths in the Philippines are shown.
Thesis (Master of Science in Public Health, Parasitology)--University of the Philippines Manila.
Keywords: Helminths -- Cultures and culture media; Helminths